IDNLearn.com is designed to help you find the answers you need quickly and easily. Get comprehensive and trustworthy answers to all your questions from our knowledgeable community members.
Sagot :
Let's pair each set of polynomials with their sum.
### Pair 1:
First set of polynomials: [tex]\(12x^2 + 3x + 6\)[/tex] and [tex]\(-7x^2 - 4x - 2\)[/tex].
To find the sum, add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ 12x^2 + 3x + 6 + (-7x^2 - 4x - 2) = (12 + -7)x^2 + (3 + -4)x + (6 + -2) \][/tex]
[tex]\[ = 5x^2 - x + 4 \][/tex]
So, the matching sum is [tex]\(5x^2 - x + 4\)[/tex].
### Pair 2:
Second set of polynomials: [tex]\(2x^2 - x\)[/tex] and [tex]\(-x - 2x^2 - 2\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ 2x^2 - x + (-x - 2x^2 - 2) = (2 + -2)x^2 + (-1 + -1)x + 0 + -2 \][/tex]
[tex]\[ = 0x^2 - 2x - 2 \][/tex]
[tex]\[ = -2x - 2 \][/tex]
So, the matching sum is [tex]\(-2x - 2\)[/tex].
### Pair 3:
Third set of polynomials: [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ x + x^2 + 2 + (x^2 - 2 - x) = (1 + 1)x^2 + (1 + -1)x + (2 + -2) \][/tex]
[tex]\[ = 2x^2 + 0x + 0 \][/tex]
[tex]\[ = 2x^2 \][/tex]
So, the matching sum is [tex]\(2x^2\)[/tex].
### Pair 4:
Fourth set of polynomials: [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8x - 2\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ x^2 + x + (x^2 + 8x - 2) = (1 + 1)x^2 + (1 + 8)x + 0 + -2 \][/tex]
[tex]\[ = 2x^2 + 9x - 2 \][/tex]
So, the matching sum is [tex]\(2x^2 + 9x - 2\)[/tex].
### Summary of Pairs:
- [tex]\(12x^2 + 3x + 6\)[/tex] and [tex]\(-7x^2 - 4x - 2\)[/tex] => [tex]\(5x^2 - x + 4\)[/tex]
- [tex]\(2x^2 - x\)[/tex] and [tex]\(-x - 2x^2 - 2\)[/tex] => [tex]\(-2x - 2\)[/tex]
- [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex] => [tex]\(2x^2\)[/tex]
- [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8x - 2\)[/tex] => [tex]\(2x^2 + 9x - 2\)[/tex]
Thus, the correct pairs are as follows:
- [tex]\(12 x^2 + 3 x + 6\)[/tex] and [tex]\(-7 x^2 - 4 x - 2\)[/tex] => [tex]\(5 x^2 - x + 4\)[/tex]
- [tex]\(2 x^2 - x\)[/tex] and [tex]\(-x - 2 x^2 - 2\)[/tex] => [tex]\(-2 x - 2\)[/tex]
- [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex] => [tex]\(2 x^2\)[/tex]
- [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8 x - 2\)[/tex] => [tex]\(2 x^2 + 9 x - 2\)[/tex]
### Pair 1:
First set of polynomials: [tex]\(12x^2 + 3x + 6\)[/tex] and [tex]\(-7x^2 - 4x - 2\)[/tex].
To find the sum, add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ 12x^2 + 3x + 6 + (-7x^2 - 4x - 2) = (12 + -7)x^2 + (3 + -4)x + (6 + -2) \][/tex]
[tex]\[ = 5x^2 - x + 4 \][/tex]
So, the matching sum is [tex]\(5x^2 - x + 4\)[/tex].
### Pair 2:
Second set of polynomials: [tex]\(2x^2 - x\)[/tex] and [tex]\(-x - 2x^2 - 2\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ 2x^2 - x + (-x - 2x^2 - 2) = (2 + -2)x^2 + (-1 + -1)x + 0 + -2 \][/tex]
[tex]\[ = 0x^2 - 2x - 2 \][/tex]
[tex]\[ = -2x - 2 \][/tex]
So, the matching sum is [tex]\(-2x - 2\)[/tex].
### Pair 3:
Third set of polynomials: [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ x + x^2 + 2 + (x^2 - 2 - x) = (1 + 1)x^2 + (1 + -1)x + (2 + -2) \][/tex]
[tex]\[ = 2x^2 + 0x + 0 \][/tex]
[tex]\[ = 2x^2 \][/tex]
So, the matching sum is [tex]\(2x^2\)[/tex].
### Pair 4:
Fourth set of polynomials: [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8x - 2\)[/tex].
Add the corresponding coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term.
[tex]\[ x^2 + x + (x^2 + 8x - 2) = (1 + 1)x^2 + (1 + 8)x + 0 + -2 \][/tex]
[tex]\[ = 2x^2 + 9x - 2 \][/tex]
So, the matching sum is [tex]\(2x^2 + 9x - 2\)[/tex].
### Summary of Pairs:
- [tex]\(12x^2 + 3x + 6\)[/tex] and [tex]\(-7x^2 - 4x - 2\)[/tex] => [tex]\(5x^2 - x + 4\)[/tex]
- [tex]\(2x^2 - x\)[/tex] and [tex]\(-x - 2x^2 - 2\)[/tex] => [tex]\(-2x - 2\)[/tex]
- [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex] => [tex]\(2x^2\)[/tex]
- [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8x - 2\)[/tex] => [tex]\(2x^2 + 9x - 2\)[/tex]
Thus, the correct pairs are as follows:
- [tex]\(12 x^2 + 3 x + 6\)[/tex] and [tex]\(-7 x^2 - 4 x - 2\)[/tex] => [tex]\(5 x^2 - x + 4\)[/tex]
- [tex]\(2 x^2 - x\)[/tex] and [tex]\(-x - 2 x^2 - 2\)[/tex] => [tex]\(-2 x - 2\)[/tex]
- [tex]\(x + x^2 + 2\)[/tex] and [tex]\(x^2 - 2 - x\)[/tex] => [tex]\(2 x^2\)[/tex]
- [tex]\(x^2 + x\)[/tex] and [tex]\(x^2 + 8 x - 2\)[/tex] => [tex]\(2 x^2 + 9 x - 2\)[/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com provides the answers you need. Thank you for visiting, and see you next time for more valuable insights.